Effect of policosanol from insect wax on amyloid β-peptide-induced toxicity in a transgenic Caenorhabditis elegans model of Alzheimer's disease - Xin Zhang; Chenjing Ma; Long Sun; Zhao He; Ying Feng; Xian Li; Jin Gan; Xiaoming Chen (BMC, 2021)
Abstract Background Alzheimer's disease (AD), an age-related neurodegenerative disorder and a serious public health concern, is mainly caused by β-amyloid (Aβ)-induced toxicity. Currently, a limited number of drugs are effective against AD, and only a few are used for its treatment. According to traditional Chinese medicine, white wax is mainly composed of policosanol, hexacosanol, and octacosanol. Policosanol has been shown to reduce lipid levels in blood and alleviate the symptoms associated with diabetic complications and neurodegenerative disorders, such as Parkinson's disease and AD. However, the efficacy of policosanol depends on the purity and composition of the preparation, and the therapeutic efficacy of policosanol derived from insect wax (PIW) in AD is unknown. Methods Here, we identified the main components of PIW and investigated the effects of PIW on Aβ-induced toxicity and life-span in a transgenic Caenorhabditis elegans model of AD, CL4176. Furthermore, we estimated the expression of amyloid precursor-like protein (apl-1) and the genes involved in various pathways associated with longevity and alleviation of AD-related symptoms in PIW-fed CL4176. Results PIW mainly consists of tetracosanol, hexacosanol, octacosanol, and triacontanol; it could decrease the Aβ-induced paralysis rate from 86.87 to 66.97% (P < 0.01) and extend the life-span from 6.2 d to 7.8 d (P < 0.001) in CL4176 worms. Furthermore, PIW downregulated apl-1, a gene known to be associated with the levels of Aβ deposits in C. elegans. Additionally, our results showed that PIW modulated the expression of genes associated with longevity-related pathways such as heat shock response, anti-oxidative stress, and glutamine cysteine synthetase. Conclusion Our findings suggest that PIW may be a potential therapeutic agent for the prevention and treatment of AD. However, its effects on murine models and patients with AD need to be explored further.